Dodging the burden of proof: A reply to Manville, Lens and Mönkkönen. (January 2022) - Rodríguez-Pose, Andrés; Storper, Michael
Manville, Lens, Mönkkönen's reply to our 'Housing, urban growth and inequalities' Urban Studies article is welcome. However, it fails to engage with our two main criticisms of the housing-as-opportunity literature: that (a) deregulation and upzoning in large and dynamic cities are unlikely to benefit those at the bottom of the income pyramid facing the greatest affordability problems; and that (b) greater deregulation will not facilitate interregional migration from low opportunity regions to booming cities, thus having no discernible impact on within-city and cross-regional inequality. We also argue that because they publicly endorse legislation making bold claims in this respect, the burden of proof lies on them and others who propose sweeping policy experiments with our cities.